A Model for Enhancing the Role of Information and Communication Technologies for Improving the Resilience of Rural Communities to Disasters. (2018) - Firdhous, M.F.M; Karuratane, P.M
Abstract: Rural communities are generally considered to be more disadvantaged than their urban counterparts in many aspects. In times of disasters too, rural population would be more vulnerable and have less opportunity to bounce back after disasters. Disasters may occur at any place, any time irrespective of the nature and the status of countries. Many lives have been lost and many more have lost their livelihoods due to disasters. It would be possible to minimize the human as well as economic losses through proper disaster management initiatives. ICT has undergone rapid advancements during the recent years and penetrated into almost every aspect of human life. ICT is an enabling technology that is capable of bridging the gap between societies. Hence ICT can be leveraged to enhance the disaster resilience of the rural communities. This paper presents an integrated model for leveraging ICT for enhancing the disaster resilience of rural communities.